2005
DOI: 10.1007/s10530-004-4062-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of an invasive alien vine, Vincetoxicum rossicum (Asclepiadaceae), on arthropod populations in Ontario old fields

Abstract: Vincetoxicum rossicum is an invasive alien vine introduced from Europe in the late 1800s that is now an emerging pest in upstate New York and eastern Ontario. The plant can form dense, monotypic stands in woodlots and old fields, and may be displacing native vegetation. As a consequence, V. rossicum may be displacing arthropod fauna associated with native vegetation. In June and August 2002, we sampled V. rossicum and three other old field plants (Asclepias syriaca, Solidago altissima, and mixed graminoids) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
65
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 18 publications
(17 reference statements)
2
65
1
1
Order By: Relevance
“…In study sites near Toronto (ON), populations were found growing on sand loams and loamy sands overlying glacial till with carbonate deposits in the upper layers indicating a fluvial origin (Christensen 1997). In Ottawa, it is often abundant in sunny undisturbed old fields (Ernst and Cappuccino 2005) and along railway lines where it forms dense stands in the well-drained ballast of the roadbeds and embankments.…”
Section: Habitatmentioning
confidence: 99%
See 1 more Smart Citation
“…In study sites near Toronto (ON), populations were found growing on sand loams and loamy sands overlying glacial till with carbonate deposits in the upper layers indicating a fluvial origin (Christensen 1997). In Ottawa, it is often abundant in sunny undisturbed old fields (Ernst and Cappuccino 2005) and along railway lines where it forms dense stands in the well-drained ballast of the roadbeds and embankments.…”
Section: Habitatmentioning
confidence: 99%
“…Cynanchum rossicum. It has been reported on the edges of alluvial woods, railroad embankments, fencerows, woods (maple, beech, oak and ash) in Ontario and western Quebec, and gardens, grassy slopes, and streambanks in southern Ontario (Moore 1959;Kirk 1985 (Ernst and Cappuccino 2005).…”
Section: Habitatmentioning
confidence: 99%
“…Competitive displacement of native plant species by Pale Swallow-wort may have negative consequences for local faunal. Ernst and Cappuccino (2005) found that diversity and abundance of both stem-and ground-dwelling arthropod species were substantially lower in patches of Pale Swallow-wort than in patches of native old-field plant species (Asclepias syriaca, Solidago altissima, and mixed graminoids). Pale Swallow-wort is also detrimental to the Monarch butterfly (Danaus plexippus) which has been observed ovipositing on it rather than on milkweed (Asclepias syriaca), THE CANADIAN FIELD-NATURALIST Vol.…”
mentioning
confidence: 94%
“…Both species are capable of growing under a range of soil and light conditions, although pale swallowwort appears to be more shade tolerant (Averill et al 2010(Averill et al , 2011DiTommaso et al 2005;Hotchkiss et al 2008;Magidow et al 2013;Smith et al 2006). Pale swallowwort reportedly reduces bird and arthropod densities in grasslands and fields (DiTommaso et al 2005;Ernst and Cappuccino 2005), and both species pose a risk to threatened and endangered species, as well as the rare alvar (limestone barrens) ecosystems in the Lower Great Lakes region (DiTommaso et al 2005;Lawlor 2000;Tewksbury et al 2002). Although both species can occupy a range of habitats, open field infestations…”
mentioning
confidence: 99%